Utilizing plasma exchange for severe cytokine release syndrome after CAR-T cell therapy: clinical experience and literature insights - Zhang, Jiasi; Xie, Dali; Tang, Meiyan; Gong, Qiang; Huang, Xingqin; Li, Ju; Xu, Shuangnian; Luo, Nan; Sun, Huiling; Tan, Fangfang (Frontiers in Immunology, 2025)
Cytokine release syndrome (CRS) is a severe complication following Chimeric Antigen Receptor T-cell (CAR-T) therapy, characterized by an excessive inflammatory response triggered by the activation of CAR-T cells. Clinically, approaches like tocilizumab and corticosteroids are commonly used to treat CRS. However, those methods might be insufficient, particularly in treating severe CRS patients (grade 3-4). Nowadays, therapeutic plasma exchange (PE) has been used as a promising adjunctive therapy to treat severe CRS, as it can rapidly remove circulating inflammatory cytokines and immune complexes which contribute to CRS progression. To summarize the characteristics and clinical usage of PE, we provide the experiences of 3 PE cases from our institution and 19 PE cases from relevant literature. In this review, we concluded that PE is effective in reducing elevated serum cytokine levels and alleviating CRS symptoms such as fever, hypotension, and neurotoxicity. Furthermore, we discuss the principles and development of PE and compare CAR-T-induced CRS with CRS caused by viral infections. In addition, PE demonstrates clear advantages over other blood purification techniques including hemofiltration (HF) and hemodiafiltration (HDF), particularly in its ability to remove large-molecular cytokines and immune complexes. To conclude, PE presents a promising therapeutic approach for managing severe CRS after CAR-T therapy, especially when standard treatments have failed.